2023
DOI: 10.1177/03000605221150136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retinal vascular density and related factors using OCTA in children and adolescents with myopia without maculopathy

Abstract: Background Myopia is the most common ophthalmic condition worldwide with a rapidly increasing prevalence. This study aimed to compare the retinal microvasculature in the superficial capillary plexus (SCP) in children and adolescents with mild and moderate/high myopia using optical coherence tomography angiography, determine the relationship between retinal parameters and axial length (AL), and understand the occurrence and progression of myopia in microcirculation. Methods This prospective observational study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…1 A recent study compared retinal microvasculature in the SCP of children and adolescents using OCTA imaging, which indicated that there were no obvious variations in microvessel density, perfusion density (PD), and the size of the foveal avascular zone within the SCP between groups with mild and moderate/high myopia. 2 Conversely, another study demonstrated a negative correlation between children's myopia diopter and the microvessel density of both the superficial and deep retinal capillary plexus in the macula, as well as retinal thickness. 3 Nonetheless, these studies only scrutinized a limited number of OCTA image parameters in the macular region and involved a relatively small number of subjects.…”
mentioning
confidence: 95%
“…1 A recent study compared retinal microvasculature in the SCP of children and adolescents using OCTA imaging, which indicated that there were no obvious variations in microvessel density, perfusion density (PD), and the size of the foveal avascular zone within the SCP between groups with mild and moderate/high myopia. 2 Conversely, another study demonstrated a negative correlation between children's myopia diopter and the microvessel density of both the superficial and deep retinal capillary plexus in the macula, as well as retinal thickness. 3 Nonetheless, these studies only scrutinized a limited number of OCTA image parameters in the macular region and involved a relatively small number of subjects.…”
mentioning
confidence: 95%